2021
DOI: 10.1002/adfm.202108794
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Asymmetric Supercapacitors with Extremely Slow Self‐Discharge Rate Enabled by a Bilayer Heterostructure Polymer Electrolyte

Abstract: Asymmetric supercapacitors (ASCs) with high working voltages, power density, and long cyclic life have attracted widespread interest. Along with their rapid charge process, the ASCs also exhibit fast self-discharge behavior, which remains a big challenge. Unfortunately, very limited studies have been focused on this crucial issue. Here, a flexible asymmetric supercapacitor with excellent electrochemical performance and ultra-long self-discharge time is reported, which is enabled by designing a bilayer heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The optimal ratio was previously optimized by our group as following. [ 36 ] 1) The pure CNTs films were immersed in concentrated nitric acid for 12 h to remove impurities and then were treated with oxygen plasma for 5 min to improve the hydrophilicity of CNTs films. 2) The treated CNTs film was used as the working electrode for electrochemical deposition, where a platinum sheet and a saturated calomel electrode (SCE) were used as counter electrode and reference electrode, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal ratio was previously optimized by our group as following. [ 36 ] 1) The pure CNTs films were immersed in concentrated nitric acid for 12 h to remove impurities and then were treated with oxygen plasma for 5 min to improve the hydrophilicity of CNTs films. 2) The treated CNTs film was used as the working electrode for electrochemical deposition, where a platinum sheet and a saturated calomel electrode (SCE) were used as counter electrode and reference electrode, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35] Recently, we for the first time introduced the bilayer heterogeneous polyelectrolyte (BHP) building by a layer of polycation complex and a layer of polyanion complex to construct two-electrode supercapacitors, which exhibited interesting suppressed effect to slowdown the self-discharge process of devices. [36,37] However, the insightful mechanism of how do the polyelectrolyte complexes affect on the electrochemical performance and self-discharge behavior of the BHP-based supercapacitors is still unclear. In this work, we designed a series of bilayer heterogeneous polyelectrolytes by using various polycation and polyanion complexes with different structures and properties and systematically investigated their effects on the electrochemical performance and self-discharge behaviors from the experimental and theoretical views.…”
Section: Introductionmentioning
confidence: 99%
“…The ambitious goal of carbon neutralization calls for high‐performance energy storage systems. [ 1,2 ] Supercapacitors have become a considerable alternative to rechargeable batteries [ 3–6 ] due to their high power density and cycle stability, especially for applications that require instantaneous high power density and short‐term energy storage, [ 7–11 ] such as the gantry cranes that need to quickly grab cargo in ports. Despite numerous advantages, self‐discharge is one of the key problems which limits the wider applications of conventional electrochemical double‐layer capacitors (EDLCs).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 More recently, heterogeneous polyelectrolytes formed by a layer of polyanion complex and a layer of polycation complex have a unique current rectification effect, 31,32 which exhibited an interesting suppressed effect on the self-discharge of flexible supercapacitors due to the electrostatic interaction force between movable ions accumulated on/in electrodes and the charged polyelectrolytes. 33,34 However, the low dissociation potential of water (1.23 V) endows the aqueous heterogeneous polyelectrolyte-based supercapacitors with a limited potential window and low energy density. [33][34][35][36] In this regard, poly(ionic liquid)s (PILs) with excellent thermal and mechanical properties of polymers also reserve the low vapor pressure and wide potential window of ionic liquids (ILs), [37][38][39] which represents a promising type of polymer gel electrolyte for high-performance flexible supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 However, the low dissociation potential of water (1.23 V) endows the aqueous heterogeneous polyelectrolyte-based supercapacitors with a limited potential window and low energy density. [33][34][35][36] In this regard, poly(ionic liquid)s (PILs) with excellent thermal and mechanical properties of polymers also reserve the low vapor pressure and wide potential window of ionic liquids (ILs), [37][38][39] which represents a promising type of polymer gel electrolyte for high-performance flexible supercapacitors. 40,41 Therefore, flexible supercapacitors with a wide potential window and slow selfdischarge rate may be achieved by designing a novel bilayer heterogeneous poly(ionic liquid) electrolyte (BHPE), but no relative research studies have been reported so far.…”
Section: Introductionmentioning
confidence: 99%